Advanced Modelling of Virtualized Servers - Kovács, Á.; Lencse, G. (Acta Technica Jaurinensis, 2016)
In the recent years, server virtualization is one of the most important directions of IT infrastructure development. Simulating virtualized infrastructures are unavoidable for designing cloud systems that are customized perfectly for a company. In this paper, we used Opennebula, Haizea and some other tools under public licenses to experiment with. We executed several experiments to examine measurement and simulation capabilities of Haizea and we also tested some typical cluster compilations from the point of view of usability and power consumption. We also tested an open source high availability web server that used virtual machines as computing resource.